1999
DOI: 10.2169/internalmedicine.38.102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Leukocytapheresis Therapy Using a Leukocyte Removal Filter in Crohn's Disease.

Abstract: Eighteen patients with active Crohn's disease were treated with one leukocytapheresis session per week for a five-week intensive therapy, decreasing to one leukocytapheresis session per month for five sessions of initial maintenance therapy. Nutritional indices, inflammatory reactions, flow cytometry profiles, and cytokine production were also assessed before and after the intensive and initial maintenance therapy. Nine of the patients (50%) attained remission at the end of the intensive therapy. The nine non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…LCAP is a therapeutic strategy involving extracorporeal immunomodulation that has been used to treat several immunological disorders including UC (8-11) and Crohn's disease (12). A multicenter, randomized controlled trial of UC patients showed that the efficacy of LCAP was significantly superior to that of high-dose steroid therapy (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LCAP is a therapeutic strategy involving extracorporeal immunomodulation that has been used to treat several immunological disorders including UC (8-11) and Crohn's disease (12). A multicenter, randomized controlled trial of UC patients showed that the efficacy of LCAP was significantly superior to that of high-dose steroid therapy (9).…”
Section: Discussionmentioning
confidence: 99%
“…LCAP was performed using a Cellsorba E column (Asahi Kasei Medical, Tokyo, Japan) installed in the extracorporeal circulation system (Plasauto LC; Asahi Kasei Medical) (6,7). For apheresis, venous access was secured via two large peripheral veins, and the blood was anticoagulated with nafamostat mesilate (Torii Pharmaceutical, Tokyo, Japan), a protease inhibitor that inhibits the activity of coagulation factors and platelet aggregation (6,7,(9)(10)(11)(12)(13)(14)(15). Heparin was not used, since its use has been associated with respiratory distress and palpitations (20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported the preliminary data by Sawada et al [55]. In another small study, 18 patients with active CD received leukocytapheresis induction treatment (1 session/week for 5 consecutive weeks), followed by a maintenance treatment (1 session/month) [68]. At the end of induction treatment, 9/18 (50%) patients achieved clinical remission.…”
Section: Cellsorba Leukocytapheresis For Crohn’s Diseasementioning
confidence: 99%
“…Currently, GMA for CD is considered as an option of medical therapy, and it is on the final stage for getting the government approval. Although LCA has been reported to have superior efficiency in patients with active CD [11], there is no sufficient data eligible for getting approval from the government.…”
Section: Cytapheresis For Patients With Crohn's Diseasementioning
confidence: 99%